A chemiluminescence metalloimmunoassay for sensitive detection of alpha-fetoprotein in human serum using Fe-MIL-88B-NH2 as a label. Issue 7 (8th August 2016) - Zhou, Jingrong; Long, Zhou; Tian, Yunfei; Ding, Xiaodong; Wu, Lan; Hou, Xiandeng
ABSTRACT: A new sensitive metalloimmunoassay using antibody labeled with metal-organic frameworks (MOFs) nanoparticles (NPs) for indirect but amplified chemiluminescence (CL) was developed for the detection of alpha-fetoprotein (AFP) in human serum. Fe-MIL-88B-NH2 NPs was prepared with a microwave-assisted synthesis approach in a facile manner, with NPs size of 50 ± 5 nm in length and 30 ± 5 nm in width. To accomplish the immunoassay of AFP, Fe-MIL-88B-NH2 NPs labeled anti-AFP was eventually dissolved in hydrochloric acid after binding with AFP for indirectly amplified signal through detection of Fe 3+ by a luminol-H2 O2 CL method. High selectivity from the immunoreaction and high sensitivity from the amplified CL were obtained for the proposed method, with a limit of detection (3 pg mL −1 ) better than those of AFP immunoassays using other methods and labeling agents including Fe-based NPs for other similar analytes. Human serum samples were analyzed for AFP by this method, with the analytical results in good agreement with those obtained by the enzyme-linked immunosorbent assay.